The End of Marketing : Humanizing Your Brand in the Age of Social Media. - Gil, Carlos. (Kogan Page, Limited, 2021)
Marketing as we know it is dead. Learn how to spend less time reaching only a limited number of followers and build more time listening to what's relevant to customers, clients and your community.